Infections after kidney transplantation: A comparison of mTOR‐Is and CNIs as basic immunosuppressants. A systematic review and meta‐analysis. Issue 3 (6th March 2020) - Wolf, Sebastian; Lauseker, Michael; Schiergens, Tobias; Wirth, Ulrich; Drefs, Moritz; Renz, Bernhard; Ryll, Martin; Bucher, Julian; Werner, Jens; Guba, Markus; Andrassy, Joachim
Abstract: Background: Side effects of the immunosuppressive therapy after solid organ transplantation are well known. Recently, significant benefits were shown for mTOR‐Is with respect to certain viral infections in comparison with CNIs. However, reported total incidences of infections under mTOR‐Is vs CNIs are usually not different. This raises the question to additional differences between these immunosuppressants regarding development and incidence of infections. Methods: The current literature was searched for prospective randomized controlled trials in renal transplantation. There were 954 trials screened of which 19 could be included (9861 pts.). The 1‐year incidence of infections, patient and graft survival were assessed in meta‐analyses. Results: Meta‐analysis on 1‐year incidence of infections showed a significant benefit of an mTOR‐I based therapy when combined with a CNI vs CNI‐based therapy alone (OR 0.76). There was no difference between mTOR‐I w/o CNI and CNI therapy (OR 0.97). For pneumonia, a significant disadvantage was seen only for mTOR‐I monotherapy compared to CNI's (OR 2.09). The incidence of CMV infections was significantly reduced under mTOR‐I therapy (combination with CNI: OR 0.30; mTOR w/o CNI: OR: 0.46). There was no significant difference between mTOR‐I and CNI therapy with respect to patient survival (mTOR‐I w/o CNI vs CNI: OR 1.22; mTOR‐I with CNI vs CNI: OR 0.86). Graft survival was negatively affected by mTOR‐I monotherapy (OR 1.52) but not when combined with a CNI (OR 0.97). Conclusion: Following renal transplantation the incidence of infections is lower when mTOR‐Is are combined with a CNI compared to a standard CNI therapy. Pneumonia occurs more often under mTOR‐I w/o CNI.